GLASSGOW COMA SCALE AND OUTCOME ON HEAD INJURY PATIENTS IN EMERGENCY ROOM AT GENERAL HOSPITAL OF PEMERINTAH ACEH - Hilman Syarif; Nova Nadila (Jurnal Keperawatan Respati Yogyakarta, 2021)
Level of conciousness on head injury patients is one of the initial assessment. Glassgow Coma Scale (GCS) is one of the methods to assess it through assessment of eyes responses, verbal responses, and motoric responses. Generally, Score of GCS related to outcome of the patients. The objective of this study was to identify score of GCS and outcome on head injury patients in emergency room at general hospital of Pemerintah Aceh. This study was quantitative and retrospective study using secondary data, medical documentation. Population are head injury patients during January to December in 2019. Sample consisted of 333 patients that identified by systematic random sampling. Tool for collecting data using observation checklist. Data analysis was using univariate analysis. Patients with GCS score 13-15 are 239 (71.8%), score 9-12 are 53 (15.9%), and score < 8 are 41 (12.3%). The mean of GCS score is 12.89 (3.19), at confidence interval 95% = 12.55-13.24. Majority outcome is inpatient about 256 (76.9%) and fewest outcome is patient back to home about 12 (3.6%). Majority of patients with the worst outcome are in GCS score <8 (82,4%). Majority score of GCS is 13-15 and inpatient outcome. Recommendation, always to conduct assessment of GCS to prevent worst outcome on patients. Keywords: Glassgow coma scale, head injury, outcome